Review of the 8th autumn school in chemoinformatics - Gasteiger, Johann (Molecular Informatics, 2024)
This paper gives an overview of the lectures and posters presented at the 8th Autumn School in Chemoinformatics held in Nara, Japan on 28th - 30th November 2023. The topics ranged from the study of chemical reactions through drug design and the use of Chemical Language Models and electronic structure informatics to the modeling of materials. In addition, a brief overview of the 50 years of work in chemoinformatics by Johann Gasteiger is given with an emphasis on the essential decisions during his scientific career.
CRIS-Team Scopus Importer:2024-10-25
Keywords: chemical reactions; drug design; electronic structure informatics; large language models; material design